PM2.5 Concentration Forecasting Using Weighted Bi-LSTM and Random Forest Feature Importance-Based Feature Selection - Baekcheon Kim; Eunkyeong Kim; Seunghwan Jung; Minseok Kim; Jinyong Kim; Sungshin Kim (Atmosphere, 2023)
Particulate matter (PM) in the air can cause various health problems and diseases in humans. In particular, the smaller size of PM<semantics>2.5</semantics> enable them to penetrate deep into the lungs, causing severe health impacts. Exposure to PM<semantics>2.5</semantics> can result in respiratory, cardiovascular, and allergic diseases, and prolonged exposure has also been linked to an increased risk of cancer, including lung cancer. Therefore, forecasting the PM<semantics>2.5</semantics> concentration in the surrounding is crucial for preventing these adverse health effects. This paper proposes a method for forecasting the PM<semantics>2.5</semantics> concentration after 1 h using bidirectional long short-term memory (Bi-LSTM). The proposed method involves selecting input variables based on the feature importance calculated by random forest, classifying the data to assign weight variables to reduce bias, and forecasting the PM<semantics>2.5</semantics> concentration using Bi-LSTM. To compare the performance of the proposed method, two case studies were conducted. First, a comparison of forecasting performance according to preprocessing. Second, forecasting performance between deep learning (long short-term memory, gated recurrent unit, and Bi-LSTM) and conventional machine learning models (multi-layer perceptron, support vector machine, decision tree, and random forest). In case study 1, The proposed method shows that the performance indices (RMSE: 3.98%p, MAE: 5.87%p, RRMSE: 3.96%p, and R<semantics>2</semantics>:0.72%p) are improved because weights are given according to the input variables before the forecasting is performed. In case study 2, we show that Bi-LSTM, which considers both directions (forward and backward), can effectively forecast when compared to conventional models (RMSE: 2.70, MAE: 0.84, RRMSE: 1.97, R<semantics>2</semantics>: 0.16). Therefore, it is shown that the proposed method can effectively forecast PM<semantics>2.5</semantics> even if the data in the high-concentration section is insufficient.